Kausalitas dalam Sains dan Teologi: Perbandingan Pandangan Mu’tazilah dan Asyariyah - Lexi Zulkarnaen Hikmah (Jurnal Peradaban, 2023)
The Mu'tazilites believed in deterministic causality explained by human reason. Humans have freedom and are responsible for their actions. Ashariyah, on the other hand, believes in occasional causality controlled by God's will. Events in the universe are not connected and only happen because of God's will. Modern science, with its developments, shows that causality is not a simple concept. From classical physics to quantum physics, understanding of causality continues to evolve and challenge traditional thinking. The meeting point between theology and modern science lies in the question of God's role in the universe. Theologians' questions about miracles and divine intervention parallel physicists' questions about cause-and-effect relationships and the behavior of objects. This journal concludes that causality is a complex and multidimensional concept that requires understanding from various perspectives, including theology and science.